Interaction of nuclear radiations with scintillation crystals ZnSe(O, Te) - Gal’chinetskii, L.P.; Ryzhikov, V.D.; Starzhinskiy, N.G. (Вопросы атомной науки и техники, 2006)
The experimental data on the irradiation of ZnSe(О,Те)-crystals with γ-quanta, protons and neutrons are presented and discussed. The mechanism for heightening the concentration of luminescence centers of C1-type ZniVZnТеSe (λmax≈640 nm) and C2-type VZnZniОSe (λmax≈605 nm), accompanied by an increase in the radioluminescence intensity, is submitted. During p-irradiation, hydrogen, generated in the process of proton thermalization, interacts with oxygen that the C2-centers contain, which results in the C2-center destruction, a decrease in the intensity and the λ max shift towards the long-wave range.